Classical Sociology Through the Lens of Gendered Experiences - Isaksson, Anna (Frontiers in Sociology, 2020)
There is a body of literature problematizing the lack of women's accounts in what is called classical sociology. However, limited efforts have been made to place female and male theorists' writings in juxtaposition with each other in order to demonstrate how their writings and theories differ. The aim of this article is to encourage discussion of how early female and male sociological theorists' descriptions and interpretations on the development of modern society were shaped by their own gendered experiences. Further, the aim is to shed light on the consequences this might provide for the teaching and learning of classical sociology. The article contributes a comparative analysis on how five authors, three female and two male, described and interpreted the transition from traditional to modern society through their gendered experiences. Their various interpretations illustrate how experiences are situated and that there is no complete and objective knowledge. As a consequence, universities should pay careful attention to gender distribution in their syllabi. Rather than achieve equal numbers of female and male authors, this will ensure that students are able to explore and understand classical sociology through the lens of different gendered experiences during their studies.